Understanding and Responding to Affectional and Transgender Prejudice and Victimization - Viehl, C.; Ginicola, M.M.; Ellis, A.; Charette, R.J. (Trauma Counseling Theories and Interventions for Managing Trauma, Stress, Crisis, and Disaster: Second Edition, 2022)
In addition to traumas that heterosexual and cisgender people experience, queer and transgender people face a heterosexist and cissexist culture, in which marginalization and trauma against them is normalized or minimized. In this chapter, the experience of hate crimes and violence, relational and interpersonal trauma, religious based-trauma, and sociocultural and political-based trauma are covered in relation to how it impacts Lesbian, Gay, Bisexual, Trans, and Queer (LGBTQ) people. Clinical and counseling implications are discussed. The increase in mental health challenges is explained via the minority stress model. Implications for diagnosis and trauma-informed practices for queer and transgender people are discussed. Additionally, the role of the mental health professional as a social justice advocate is explored, including how social justice frameworks can be incorporated in the counseling environment. © 2023 Springer Publishing Company, LLC and 2012. All rights reserved.
Keywords: dept.csp

Autism and intersectionality: Considerations for school-based practitioners - Sassu, Kari A.; Volkmar, Fred R. (Psychology in the Schools, 2022)
The purpose of this article is to explore the intersectionality of autism and sociocultural factors as well as discuss the complexities associated with appropriate assessment, diagnosis, and intervention. Based on a review of the literature, the authors present a brief history of the emergence of the term autism and highlight factors that have contributed to current concerns about failures to appropriately recognize autism within diverse populations. Referencing extant research as well as professional practice standards, this article examines aspects of autism and intersectionality, and explores some of the associated challenges related to assessment, diagnosis, and intervention. Further, the authors reflect on the critical importance of carefully considering all aspects of a child's identity when engaging in autism assessment and intervention within the school setting. School-based practitioners are provided with guidance for addressing the needs of diverse populations of students with autism.
Keywords: SES; autism; dept.csp; dept.sed; ethnicity; intersectionality; peer-reviewed; race